Quantile Methods for Complex Financial Systems - Final Report of the project under the DFG-Individual Research Grants Programme - Melanie Schienle; Weining Wang (ZBW - Leibniz Information Centre for Economics, 2023)
Financial systems have become increasingly complex. They are characterized by their large dimensional, strong cross-sectional dependence amounting to networks of unknown and time-varying form which appear as main drivers of risk of and within the system. Moreover, in turbulent market times, accurate estimation and prediction of systemic and idiosyncratic risk requires novel econometric and statistical models and techniques that account for the network topology but also for macro- and micro-economic factors and determinants in order to quickly adjust and respond to changing environments. In this project, we provide innovative techniques to better estimate and predict moderate and extreme risk in complex systems. This is of key interest for financial market participants and for prudential supervisors, but also delivers solutions for a better understanding of other complex systems such as electricity markets. We focus on econometric methodologies for conditional quantiles directly related to the Value-at-Risk (VaR) concept for risk measurement. Though, all presented approaches are readily extendible to further risk measures such as expected shortfall or others. In particular, we have developed statistical concepts for (tail) networks uncovering novel structural risk channels within large dimensional financial systems and for determining suitable tail factors for accurate prediction. Beyond that, we have developed novel techniques that address further challenges in dynamic networks such as their dynamic evolu-tion, high-dimensionality, nonstationarity and causal effect identification. For the general public, we have graphically illustrated and maintained the practical impact on financial systemic risk measurement of many of our techniques on the companion website http://frm.wiwi.hu-berlin.de.
Keywords: 330